Metal sputtered graphene based hybrid films comprising tin oxide/reduced graphene oxide/Ni as electrodes for high-voltage electrochemical capacitors. (April 2018) - Byun, Segi; Shin, Byungha; Yu, Jin
Abstract: The high voltage aqueous electrochemical capacitor (EC) is a promising energy storage device because of eco-friendliness and high electrochemical performance with a wide operational voltage and high energy density. However, it typically experiences a stability problem that includes cell aging and capacitance loss. Here, to overcome the stability issue, a thin metal layer of Ni is created on one side of a SnO2 /reduced graphene oxide (rGO) hybrid film to produce a binder-free film of SnO2 /rGO/Ni. Due to the formation of the highly conductive metal layer of Ni, the fabricated film can be well interconnected with the current collector and have lower contact resistance and open-circuit potential compared with untreated SnO2 /rGO film, which results in a remarkable enhancement of electrochemical performance, including a wide operational voltage (1.8 V), semi-permanent cycle-life (95% retention after 10k cycles), and ultrahigh volumetric energy density with a high power density, all of which are superior values compared to bare SnO2 /rGO film based devices. We anticipate that the fabricated SnO2 /rGO/Ni film could be utilized as a promising electrode for high voltage ECs, and our simple surface engineering technique will provide an effective electrode design for the fabrication of high performance thin-film ECs. Graphical abstract: Forming a highly conductive metal layer of Ni on the SnO2 /rGO based electrode can be dramatically enhanced the electrochemical performance. Image 1